Reflections on Creative Recruiting Solutions to the Nationwide Nursing Shortage - Shepherd, Ethan H.; Shepherd, Ian J.; Vardiman , Phil (Journal of Management Policy and Practice, 2024)
There is possibly no nobler profession than the field of nursing. An individual selflessly cares for another human being, working long hours for little pay. With the aging population in the United States, there has been a shortage of nurses that can effectively meet the needs of patients. Hospitals are developing new incentives to attract and retain top talent. This paper will review relevant literature on the nationwide nursing shortage. It will show that this is not a new phenomenon, unique only to the United States. We will compare recruiting strategies from the past and develop best practices for recruiting and retention in today’s competitive market. An applicable hiring model will be presented.